Role of Organic Loading Rate in Bioenergy Generation from Palm Oil Mill Effluent in a Two-Stage Up-Flow Anaerobic Sludge Blanket Continuous-Stirred Tank Reactor - Santhana, Krishnan; Singh, Lakhveer; Mimi Sakinah, A. M.; Thakur, Sveta; Zularisam, A. W.; Ghrayeb, Omar A. (Elsevier, 2017)
This contribution presents the technical possibilities for continuous hydrogen and methane production using an optimum organic loading rate of palm oil mill effluent in a two-stage reactor at a thermophilic temperature of 55 °C. The influence of four organic loading rates, namely, 30, 40, 50, and 60 kg COD/(m3 d) for hydrogen production and 8.3, 10.2, 13.1, 15.8 kg COD/(m3 d) for methane production, were investigated. Hydrogen production was controlled in an up-flow anaerobic sludge blanket reactor at a constant hydraulic retention time of 12 h. The maximum hydrogen content, volumetric hydrogen production rate and hydrogen yield were found to be 45%, 2.5 L H2/d and 33.48 mL H2/g COD, respectively, at the organic loading rate of 50 kg COD/(m3 d). The effluent from the hydrogenogenic reactor was further digested into methane in the continuous stirred tank reactor at a hydraulic retention time of 5 d. The maximum volumetric methane production rate and methane yield were 10.58 L CH4/d. and 0.11 m3 CH4/kg COD, respectively, at an organic loading rate of 13.1 kg COD/(m3 d). A total chemical oxygen demand removal of 91% was achieved in this two-stage process. The scientific contribution of this two-stage technology with an optimized organic loading rate may play a significant role in degrading palm oil mill effluent and developing an energy-efficient strategy for waste management.